Dietary supplementation of squalene increases the growth performance of early-weaned piglets by improving gut microbiota, intestinal barrier, and blood antioxidant capacity - Gao, Yang; Ma, Xue; Zhou, Yingqing; Li, Yongqiang; Xiang, Dong (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary squalene (SQ) supplementation on the growth performance of early-weaned piglets. Twenty early-weaned piglets were randomly divided into two groups, the squalene group (SQ) and the control group (CON). The CON group was fed a basal diet, and the SQ group was fed a basal diet with 250 mg/kg squalene. The feeding period lasted 21 days. The results showed that SQ significantly increased the final body weight (FWB, P < 0.05), average daily gain (ADG, P < 0.05), and average daily feed intake (ADFI, P < 0.05) and significantly decreased the F/G ratio (feed intake/gain, P < 0.05) and diarrhea index (DI, P < 0.05). In terms of blood biochemical indicators, SQ significantly increased anti-inflammatory factors such as transforming growth factor-β (TGF-β, P < 0.001), interleukin-10 (IL-10, P < 0.001), and interferon-γ (IFN-γ, P < 0.01), and decreased pro-inflammatory factors such as tumor necrosis factor-α (TFN-α, P < 0.001) and interleukin-6 (IL-6, P < 0.001). Furthermore, SQ significantly increased blood antioxidant indexes (P < 0.001) such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and total antioxidant capacity (T-AOC) and significantly decreased the level of malondialdehyde (MDA) (P < 0.001). The villus height (P < 0.001) and V/C ratio (villus height/crypt depth, P < 0.001) of the jejunum were significantly increased in the SQ group, while the crypt depth (P < 0.01) was decreased compared to the CON group. The intestinal permeability indexes, namely diamine oxidase (DAO), D-lactic acid (D-Lac), regenerative insulin-derived protein 3 (REG-3), and FITC-Dextran 4 (FD4), significantly decreased the concentrations in the treatment group (P < 0.001), and the antioxidant indexes of the jejunum, such as SOD, GSH-Px, CAT, and MDA, were improved by adding SQ. The qPCR results showed that adding SQ could significantly increase the mRNA expression of jejunal tight-junction proteins, such as zonula occludens-1 (ZO-1, P < 0.001), Occludin (P < 0.001), Claudin (P < 0.001), glucagon-like peptide-2 (GLP-2, P < 0.001), and insulin-like growth factor-1 (IGF-1, P < 0.001). Then, we used Western blotting experiments to further confirm the qPCR results. In addition, it was found that adding SQ increased the abundance of beneficial bacteria such as Gemmiger (P < 0.01) and decreased the abundance of harmful bacteria such as Alloprevotella (P < 0.05), Desulfovibrio (P < 0.05), and Barnesiella (P < 0.05). It was interesting that there was a very close correlation among the fecal microbes, growth performance parameters, intestinal barrier, and blood biochemical indicators. In conclusion, the data suggest that SQ supplementation could effectively improve the growth performance of early-weaned piglets by improving the gut microbiota, intestinal barrier, and antioxidant capacity of the blood and jejunal mucosa.